2019
DOI: 10.1111/ijcp.13384
|View full text |Cite
|
Sign up to set email alerts
|

The association of erectile dysfunction with productivity and absenteeism in eight countries globally

Abstract: Aim:To evaluate the association of erectile dysfunction (ED) with work productivity loss, activity impairment and health-related quality of life (HRQoL) across Brazil, China, France, Germany, Italy, Spain, the UK and the US. Methods:This cross-sectional observational study used data from adult men (40-70 years old; N = 52 697) from the 2015 and 2016 National Health and Wellness Surveys. ED assessment was based on self-reported difficulty in achieving or maintaining an erection in the past 6 months. Impairment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 37 publications
(48 reference statements)
2
41
0
Order By: Relevance
“…Employersponsored insurers with a ben efit exclusion for ED treatment undercut the determination of medically necessary treatment made by licensed med ical professionals and the medical policies developed and published by the health insurance companies that administer their benefits. The exclusions for ED treat ment ultimately negatively affect employers as they have implications for employee satisfaction and retention (Fabius et al, 2013;Goetzel et al, 2016;Goldstein, Goren, Li, Maculaitis, et al, 2019;Grossmeier et al, 2016). Policy wording that facilitates healthcare provid ers' implementation of treatment guidelines supports gender equity for reproductive health care by enabling access to medically necessary ED treatment.…”
Section: Call To Action To Improve Consistency and Accessibility Of Ementioning
confidence: 99%
See 4 more Smart Citations
“…Employersponsored insurers with a ben efit exclusion for ED treatment undercut the determination of medically necessary treatment made by licensed med ical professionals and the medical policies developed and published by the health insurance companies that administer their benefits. The exclusions for ED treat ment ultimately negatively affect employers as they have implications for employee satisfaction and retention (Fabius et al, 2013;Goetzel et al, 2016;Goldstein, Goren, Li, Maculaitis, et al, 2019;Grossmeier et al, 2016). Policy wording that facilitates healthcare provid ers' implementation of treatment guidelines supports gender equity for reproductive health care by enabling access to medically necessary ED treatment.…”
Section: Call To Action To Improve Consistency and Accessibility Of Ementioning
confidence: 99%
“…Evidence has reported that a healthy and engaged work force correlates with exceptional company financial performance (Fabius et al, 2013;Goetzel et al, 2016;Grossmeier et al, 2016). Allowing access to medically necessary health benefits such as ED treatment could benefit employers through increased productivity, loy alty, and retention as well as decreased absenteeism and presentism rates (Fabius et al, 2013;Goetzel et al, 2016;Goldstein, Goren, Li, Maculaitis, et al, 2019;Grossmeier et al, 2016).…”
Section: Implications Of Employer Exclusion Of Ed Treatmentmentioning
confidence: 99%
See 3 more Smart Citations